Horizon 2020: The Grand Challenges Challenges and Opportunities - Žic Fuchs, Milena (Array, 2012)
Presentation focused on the role of SSH research in Grand Challenges as well as the so-called Sixth Grand Challenge, dedicated specifically to the Humanities and Social Sciences. The importance of Infrastructures in SSH as well as the global dimension of research were stressed.